Can allergy patch tests with food additives help to diagnose the cause in childhood chronic spontaneous urticaria? - ÖZKAYA, EMİN; Ozceker, Deniz; Dilek, Fatih; Yucel, Esra; Tamay, Zeynep; ÖZKAYA, EMİN; Guler, Nermin (My University, 2020)
Introduction: Chronic spontaneous urticaria (CSU) is characterized by the onset of symptoms which are not induced by specific triggers, but are rather spontaneous. A considerable number of patients report that foods or food additives might be responsible for their chronic urticaria.